An online collision-free trajectory generation algorithm for human–robot collaboration - Wang, Yanzhe; Wei, Lai; Du, Kunpeng; Liu, Gongping; Yang, Qian; Wei, Yanding; Fang, Qiang (Robotics and computer-integrated manufacturing, 2023)
The premise of human–robot collaboration is that robots have adaptive trajectory planning strategies in hybrid work cell. The aim of this paper is to propose a new online collision avoidance trajectory planning algorithm for moderate dynamic environments to insure human safety when sharing collaborative tasks. The algorithm contains two parts: trajectory generation and local optimization. Firstly, based on empirical Dirichlet Process Gaussian Mixture Model (DPGMM) distribution learning, a neural network trajectory planner called Collaborative Waypoint Planning network (CWP-net) is proposed to generate all key waypoints required for dynamic obstacle avoidance in joint space according to environmental inputs. These points are used to generate quintic spline smooth motion trajectories with velocity and acceleration constraints. Secondly, we present an improved Stochastic Trajectory Optimization for Motion Planning (STOMP) algorithm which locally optimizes the generated trajectories of CWP-net by constraining the trajectory optimization range and direction through the DPGMM model. Simulations and real experiments from an industrial use case of human–robot collaboration in the field of aircraft assembly testing show that the proposed algorithm can smoothly adjust the nominal path online and effectively avoid collisions during the collaboration. •An online trajectory planning algorithm for dynamic obstacles avoidance is proposed.•A neural network CWP-net with multiple collision-free waypoints output is designed.•An improved STOMP algorithm is proposed for local trajectory optimization.•Continuous smooth trajectories are generated and satisfy joint constraints.•This work builds a bridge between advanced offline planners and online planning tasks.